P-BBA: A MASTER/SLAVE PARALLEL BINARY-BASED ALGORITHM FORMINING FREQUENT ITEMSETS IN LARGE-SCALE DATASETS - AMIR, ALIYA NAJIHA (2021)
Frequent itemsets mining is an effective but computationally expensive technique, especially when dealing with big datasets.